Contaminação microbiológica dos tetos de vacas leiteiras mantidas em sistema de confinamento Compost Barn - Fogaça, Carolina dos Santos Sousa (Universidade Federal de São Carlos, 2021)
The health of the udder of cows is strictly correlated to the absence of inflammatory processes that can affect the mammary gland, such as mastitis, which is considered the disease with the greatest impact on economic and productive aspects in dairy farming worldwide. Due to the high incidence of this disease in dairy cattle, an alternative system to the Free-Stall model, called Compost Barn, was developed. Therefore, this project aimed to establish the relationship between a Compost Barn confinement system and the contaminating microbiota of cow teats. In a rural property in the city of Angatuba - SP, monthly collections of materials were carried out in 10 % of the herd of cows, divided into three lots, and in specific points of the compost bed used in the confinement barn. For the cows, samples were collected with the aid of swabs on the outside of the sphincter of each teat and for the compost bed, plastic bags were used to collect and mix the samples. Subsequently, aliquots of decimal dilutions were transferred to Petri dishes with culture medium for analysis of total coliforms and Staphylococcus spp. of the udder and for analysis of total coliforms in the bed. The average coliform count per udder was 2.8 Log10 CFU/udder for lot 1, 2.7 Log10 CFU/udder for lot 2, and 3.0 Log10 CFU/udder for lot 3, with a level of 2.84 ± 0.55 Log10 CFU/udder (mean SE; N = 33), with CV = 19.30 %. For Staphylococcus spp., the mean count of lot 1 was 5.3 Log10 CFU/udder, of lot 2 it was 5.5 Log10 CFU/udder and of lot 3 it was 5.3 Log10 CFU/udder, with level of 5.35 ± 0.45 Log10 CFU/udder (mean SE; N = 33), with CV of 8.48 %. According to the methodology, the compost bed of the confinement system was also analyzed for the concentration of total coliforms, with the average counts per bed of each batch being 5.7 Log10 CFU/g of sample from batch 1, while in the beds of lots 2 and 3 were 5.5 Log10 CFU/g, with coliform level at 5.55 ± 0.50 Log10 CFU/g (mean SE; N = 36), with CV = 9.03 %. Through the obtained results, it appears that the Compost Barn confinement system has been shown to be effective in relation to the low count of Staphylococcus spp. and total coliforms in the udder and barn compost bed.
Microbiological contamination of dairy cow teats kept in a Compost Barn feedlot system
Keywords: Vacas leiteiras; Mastite; Microbiota contaminante; Dairy cows; Mastitis; Contaminant microbiota; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA